2016
DOI: 10.1039/c5tc03448e
|View full text |Cite
|
Sign up to set email alerts
|

Real-time evaluation of thin film drying kinetics using an advanced, multi-probe optical setup

Abstract: a Solution-processed organic photovoltaic devices are advantageous due to their low-cost large area manufacturing techniques, such as slot-die coating, gravure printing and roll-to-roll coating. The final microstructure of a polymer:fullerene bulk-heterojunction (BHJ) film is a fine interplay between solution thermodynamics (e.g. solubility, miscibility. . .) and kinetics (e.g. solvent evaporation, polymer ordering, phase separation. . .) during the drying process. In order to design better performing organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 40 publications
2
49
0
Order By: Relevance
“…36,38 The LS signal of the additive-free sample (Fig. 7b) showed a sharp increase right before drying and stabilized quickly with the completion of drying.…”
Section: In Situ Characterizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…36,38 The LS signal of the additive-free sample (Fig. 7b) showed a sharp increase right before drying and stabilized quickly with the completion of drying.…”
Section: In Situ Characterizationsmentioning
confidence: 99%
“…38 We were able to attain a complete picture on the interplay between the thermodynamic and kinetic processes, governing the drying. In particular from in situ PL measurements, we concluded that the microstructure formation of additive-free DPP-TT-T : PCBM was dominated by the solubility limit of the polymer in o-xylene which caused a solid-liquid phase separation-induced gelation, hindering the crystal growth.…”
Section: In Situ Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the drying pathway has been recognised by several authors and has been found to considerably impact performances. [22][23][24]…”
Section: Annealing Protocolsmentioning
confidence: 99%
“…14,15,[18][19][20][21][22][23] Recent processing approaches, however, have not always been able to overcome the complexity of separating intrinsic from extrinsic effects.…”
Section: 13mentioning
confidence: 99%